Thermodynamics Theoretical Investigation for Synthesis of Pyridine from Pyrylium Salt using Density Functional Theory - Khoiriah, Selmi F.; Aprianto, Agil; Kania, Putri; Fauzi, Rafi N.; Nurhayati, Mita (Jurnal Kartika Kimia, 2022)
Pyridine is a heterocyclic compound that is widely used as an ingredient in medicines, vitamins, food flavors, pesticides, dyes, adhesives, and others. Currently, pyridine synthesis is carried out with coal tar as a raw material, which is a non-renewable natural resource. In this research, a theoretical study was carried out to evaluate the synthesis process of pyridine using pyrylium salt as an alternative raw material to displace coal tar. This study also aims to simulate the pyridine synthesis and the energy required or released in the process. Density Functional Theory (DFT) method was employed to calculate some thermodynamic properties of the species involved in the reaction such as enthalpy, entropy, and Gibbs free energy in a vacuum and solvated model in order to study the progress of the reaction and mechanism. Based on the calculation results, the lowest value of enthalpy, entropy, and free energy Gibbs is obtained when the reaction takes place in a vacuum. The change of entropy and free Gibbs energy of the reaction was not predominantly affected by the degree of polarity of the solvent. Meanwhile, the enthalpy of reaction simulated in water solvent is higher than in the ethanol solvent. The synthesis reaction of pyridine from pyrylium salt is exothermic and exergonic because it has a negative value of enthalpy change and Gibbs free energy at 298.15 K, which is potential to be done at room temperature without extreme condition control.